Treatment of angina pectoris with nifedipine and atenolol: efficacy and effect on cardiac function. Issue 3 (March 1986) - Findlay, I N; MacLeod, K; Ford, M; Gillen, G; Elliott, A T; Dargie, H J
Abstract : The antianginal effects of nifedipine 20 mg three times a day and atenolol 100 mg once a day singly and in combination were investigated in 16 patients with angina pectoris. The amount of work that could be done before angina and ST depression appeared was significantly increased by atenolol and the combination but not by nifedipine. At peak exercise the number of leads on a 16 point precordial electrocardiogram map that demonstrated greater than or equal to 1 mm ST segment depression was significantly reduced from a mean (SD) of 5.0 (0.4) on placebo to 3.7 (0.6), 2.8 (0.4), and 2.3 (0.7) on nifedipine, atenolol, and the combination respectively. Mean resting left ventricular ejection fraction, assessed by gated radionuclide ventriculography, did not change during any active treatment phase but increased significantly during exercise only on nifedipine and the combination. The nifedipine/atenolol combination was the most effective treatment, and the data suggest that nifedipine may be used to best advantage in combination with a beta blocker.